Peran Literasi dan Inklusi Keuangan Terhadap Prilaku Keuangan di Masa Pandemi ( Study Kasus pada UMKM Kabupaten Buleleng ) - Wayan Sugita; Ni Kadek Sinarwati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of financial literacy and inclusion on the financial behavior of MSME managers in Buleleng Regency. This research is a type of quantitative research with the number of respondents as many as 71 MSMEs in Buleleng Regency. Data obtained by distributing questionnaires. The sample was selected using criteria with purvosive sampling technique and then calculated using the Slovin formula. The data used is primary data in the form of respondents' answers and analyzed by path analysis assisted by SmartPLS Ver software. 3.0.. The results show that financial literacy and inclusion affect the financial behavior of MSME managers.Keywords: literasi , Inklusi , MSMEs